Interaural speech asymmetry predicts bilateral speech intelligibility but not listening effort in adults with bilateral cochlear implants - Emily A. Burg; Emily A. Burg; Tanvi D. Thakkar; Ruth Y. Litovsky; Ruth Y. Litovsky; Ruth Y. Litovsky (Frontiers in Neuroscience, 2022)
IntroductionBilateral cochlear implants (BiCIs) can facilitate improved speech intelligibility in noise and sound localization abilities compared to a unilateral implant in individuals with bilateral severe to profound hearing loss. Still, many individuals with BiCIs do not benefit from binaural hearing to the same extent that normal hearing (NH) listeners do. For example, binaural redundancy, a speech intelligibility benefit derived from having access to duplicate copies of a signal, is highly variable among BiCI users. Additionally, patients with hearing loss commonly report elevated listening effort compared to NH listeners. There is some evidence to suggest that BiCIs may reduce listening effort compared to a unilateral CI, but the limited existing literature has not shown this consistently. Critically, no studies to date have investigated this question using pupillometry to quantify listening effort, where large pupil sizes indicate high effort and small pupil sizes indicate low effort. Thus, the present study aimed to build on existing literature by investigating the potential benefits of BiCIs for both speech intelligibility and listening effort.MethodsTwelve BiCI adults were tested in three listening conditions: Better Ear, Poorer Ear, and Bilateral. Stimuli were IEEE sentences presented from a loudspeaker at 0° azimuth in quiet. Participants were asked to repeat back the sentences, and responses were scored by an experimenter while changes in pupil dilation were measured.ResultsOn average, participants demonstrated similar speech intelligibility in the Better Ear and Bilateral conditions, and significantly worse speech intelligibility in the Poorer Ear condition. Despite similar speech intelligibility in the Better Ear and Bilateral conditions, pupil dilation was significantly larger in the Bilateral condition.DiscussionThese results suggest that the BiCI users tested in this study did not demonstrate binaural redundancy in quiet. The large interaural speech asymmetries demonstrated by participants may have precluded them from obtaining binaural redundancy, as shown by the inverse relationship between the two variables. Further, participants did not obtain a release from effort when listening with two ears versus their better ear only. Instead, results indicate that bilateral listening elicited increased effort compared to better ear listening, which may be due to poor integration of asymmetric inputs.